Callus Proliferation from Immature Leaf Explants of Durian (Durio zibethinus Murr. cv. Selat) with the Addition of Picloram and BAP - Zulkarnain ,; , Lizawati (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTThis study was aimed to obtain an appropriate medium composition with various combinations of Picloram + BAP for the proliferation of embryogenic callus from immature leaf explants of durian. The experiment was carried out at the Plant Biotechnology Laboratory, Faculty of Agriculture , the University of Jambi from January through to November 2012. Five levels of Picloram (1.0, 2.0, 3.0, 4.0, 5.0 mg L-1) in combination with three levels of BAP (0, 0.5, 1.5 mg L-1) were tested. Therefore, there were 15 treatment combinations with 4 replicates resulting in 60 experimental unit. Each unit consisted of 4 culture flasks containing one immature leaf explant. Cultures were kept in culture room with 16 h photoperiod and 1000 lux light intensity. The results showed that: 1) callus proliferation on immature leaf explants of durian cv. Selat was dependent upon the level of Picloram + BAP added to culture medium, 2) the addition of 3.0 - 5.0 mg L-1Picloram without BAP was found to be effective in promoting callus proliferation on the majority of cultured explants, 3) all regenerated callus showed similar characteristics, but embryogenic properties was not seen yet, and 4) the application of tissue culture technique in the propagation of durian cv. Selat needs further comprehensive investigation, particularly on factors directly affecting culture development and inducing somatic embryogenesis.Key words: tissue culture, in vitro culture, micropropagation, plant hormones, auxin, cytokinin, fruit crops. ABSTRAKPenelitian ini bertujuan untuk mendapatkan komposisi media yang tepat dari kombinasi Picloram + BAP untuk proliferasi kalus embriogenik dari eksplan daun dewasa durian. Penelitian dilakukan di Laboratorium Bioteknologi Tanaman, Fakultas Pertanian, Universitas Jambi dari Januari hingga November 2012. Perlakuan kombinasi media zat pengatur tumbuh adalah lima taraf Picloram (1.0, 2.0, 3.0, 4.0, 5.0 mg L-1) dengan kombinasi tiga taraf perlakuan BAP (0, 0.5, 1.5 mg L-1). Terdapat 15 kombinasi media perlakuan dengan 4 ulangan, sehingga terdapat 60 kombinasi satuan percobaan. Setiap unit percobaan terdapat 4 botol kultur dengan satu eksplan daun. Kultur disimpan di ruang kultur selama 16 jam penyinaran dan intensitas cahaya 1000 lux. Hasil penelitian menunjukkan bahwa: 1) Proliferasi kalus dari eksplan daun muda buah durian tergantung pada taraf kombinasi picloram + BAP yang ditambahkan ke media kultur; 2) Penambahan 3.0-5.0 mg L-1Picloram tanpa BAP memberikan hasil yang efektif untuk menginduksi proliferasi kalus pada sebagian besar eksplan; 3) Regenerasi kalus menunjukkan karakteristik serupa, tetapi embriogenik kalus tidak muncul, dan 4) Perbanyakan eksplan daun durian dengan tehnik kultur jaringan membutuhkan penelitian lebih lanjut, terutama pada faktor yang berpengaruh langsung pada induksi embriogenesis somatik.Kata kunci: auksin, buah, kultur jaringan, kultur in vitro, mikropropagasi, sitokinin, zat pengaturtumbuh,